Effectiveness of psychosocial interventions for pediatric patients with scoliosis: a systematic review - Connie Wong; Maike van Niekerk; Ann Richey; John Vorhies; Kali Tileston (BMJ Publishing Group, 2023)
Background Pediatric patients affected by scoliosis have complex psychological and social care needs, and may benefit from psychosocial interventions. We therefore aimed to summarize evidence of the efficacy of psychosocial interventions for this patient population.Methods Literature was identified by searching Medline, PsycINFO, Embase, EBSCO Cumulated Index to Nursing and Allied Health Literature (CINAHL), and Cochrane Central Register of Controlled Trials (CENTRAL) from database inception to 20 March 2022. Articles that evaluated the effectiveness of psychosocial interventions for pediatric patients diagnosed with scoliosis and reported at least one quantitative outcome were included. Article eligibility, data extraction, and quality assessment (using the Cochrane Collaboration's Risk of Bias Tool and Methodological Index for Non-Randomized Studies) were performed by two independent researchers. Findings are presented using narrative synthesis.Results We identified ten studies, all of which focused on adolescent idiopathic scoliosis. Studies included a total of 1007 participants, most of whom were female. Three studies focused on patients undergoing bracing, six on patients undergoing spinal surgery, and one on patients broadly. Brace compliance monitoring and counseling were found to significantly improve brace compliance quality and quantity. Proactive mental healthcare delivery by nurses after spinal surgery was similarly found to improve outcomes. Several studies examined the efficacy of brief educational interventions; most did not report clear evidence of their efficacy. The methodological quality of studies was often unclear due to limitations in articles' reporting quality.Conclusions Research on the efficacy of psychosocial interventions for pediatric patients with scoliosis is limited, with interventions involving frequent patient-provider interactions showing the most promise. Future clinical and research efforts should focus on developing and testing psychosocial interventions for this patient population, with emphasis on multidisciplinary teams delivering holistic care.Trial registration number PROSPERO number CRD42022326957